TO FORMULATE AND EVALUATE A HERBAL MOISTURIZING CREAM USING NATURAL PLANT EXTRACTS AND OILS FOR SKIN HYDRATION AND PROTECTION - Omkar Umesh Jadhav,; Karishma Rajendra Jathar,; Abhishek Dada Lahor,; Akshy Santosh Pawar,; Sohan Rajendra Londhe,; Aditya Anil Thakare,; Rahul Maruti Chavan,; Vijayshri Ramchandra Waghmode,; Rutuja Devidas Lagad,; Vikram Jaysingh Pansare,; Dr. Amol Navnath Khedkar, (The Bioscan, 2026)
The present study was carried out to formulate and evaluate an herbal moisturizing cream using natural plant extracts and oils for skin hydration and protection. The formulation contained Tagetes erecta (Marigold), Aloe barbadensis Miller (Aloe vera), coconut oil, Vitamin E, bees wax, jasmine oil, and licorice, which possess moisturizing, antioxidant, soothing, and skin-protective properties. The cream was prepared by suitable heating and mixing methods and evaluated for appearance, odor, homogeneity, pH, spreadability, washability, and irritancy. The results showed that the formulation had a smooth texture, good spreadability, acceptable pH, and satisfactory stability. No signs of skin irritation were observed during the irritancy study. The study concluded that the formulated herbal moisturizing cream is safe, stable, and effective for maintaining skin hydration and protecting the skin from dryness.